2017
DOI: 10.1186/s12871-016-0294-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fresh gas flow rate and type of anesthesia machine on time to reach target sevoflurane concentration

Abstract: BackgroundAnesthesia machines have been developed by the application of new technology for rapid and easier control of anesthetic concentration. In this study, we used a test lung to investigate whether the time taken to reach the target sevoflurane concentration varies with the rate of fresh gas flow (FGF) and type of anesthesia machine (AM).MethodsWe measured the times taken to reach the target sevoflurane concentration (2 minimum alveolar concentration = 4%) at variable rates of FGF (0.5, 1, or 3 L/min) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Our results also show that Maplesons mathematical calculations of a theoretical optimal FGF at around 4 l/min were accurate 6 . The result is also in line with what Shin et al found in their study: increasing the FGF from low flow to moderately high flow will decrease the wash-in time 7 . However, our results show that there seem to be no benefits to raising the FGF to levels of 6 l/min and above while performing a wash-in.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also show that Maplesons mathematical calculations of a theoretical optimal FGF at around 4 l/min were accurate 6 . The result is also in line with what Shin et al found in their study: increasing the FGF from low flow to moderately high flow will decrease the wash-in time 7 . However, our results show that there seem to be no benefits to raising the FGF to levels of 6 l/min and above while performing a wash-in.…”
Section: Discussionsupporting
confidence: 92%
“…et al performed a wash-in study using a Primus anesthetic machine connected to a test-lung, using a FGF of 0.5, 1, and 3 L•min − 1 and setting the F V S to 6%. The respective mean time to reach a F A S of 4% for each FGF was 1165, 534, and 155 s [13]. The latter 3 studies were, however, all performed in test-lungs such that the uptake of sevoflurane by body tissues was not considered, so the results cannot be generalized to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Shin and colleagues performed a wash-in 6 study using a Primus anesthetic machine connected to a test-lung, using a FGF of 0.5, 1, and 3 L•min-1 and setting the FVS to 6%. The respective mean times to reach FAS of 4% for each FGF were 1,165, 534, and 155 sec [13]. The latter 3 studies were, however, all performed in test-lungs such that the uptake of sevoflurane by body tissues was not considered.…”
Section: Discussionmentioning
confidence: 99%